A Study on the Structural Safety of Buildings using Image Metrology - Alademomi, Alfred Sunday; Atojunere, Eganoosi Esme; Salami, Tosin Julius; Alabi, Abiodun Olawale; Jimoh, Olalekan Abeeb; Ishola, Sunday Amos; Ayantayo-Ojo, Inioluwa Victor; Odumosu, Joseph Olayemi (Engineering, Technology & Applied Science Research, 2024)
This research aims to explore the potential of image metrology as a substitute for monitoring building structural deformations. It utilizes stereo-photogrammetry and the Kalman filter in its approach. The ultimate goal is to reduce the damage to human lives and property caused by the collapse of building structures in urban areas. Image metrology and conventional geodetic surveying were both used in monitoring the deformation of a selected building prone to land subsidence. Four geodetic monitoring stations were established using the GNSS surveying technique, while 10 photo points were placed on the selected building for deformation monitoring. Simultaneous observation of photo points and acquisition of their images were carried out during the first three months of this study. The data acquired via geodetic survey were subjected to least square adjustment while the images acquired were subjected to stereo-photogrammetry and Kalman filtering for extraction and refinement of photo point coordinates. The preliminary results show that image metrology is comparable to conventional geodetic survey methods for monitoring building deformation down to 100 mm. The t statistic value of 1.524234 and t critical value of 1.7291333 justify the comparability.